Legal force of PPJB if not registered at the land office according to article 127 letter B of Permen ATR/KBPN number 16 year 2021 - Firyal Arva Ovala; FX. Arsin Lukman (The International Journal of Politics and Sociology Research, 2023)
The background of this research is the release of the provisions of Article 127 Letter B Permen ATR/Ka-BPN Number 16 regarding the registration of a Sale and Purchase Agreement (PPJB). Based on this background, the purpose of this research is to examine: (1) the legal position of PPJB in buying and selling transactions; (2) the legal effect of PPJB registration to the Land Office on the legal status of PPJB. This research approach is qualitative. Secondary data collection techniques through satisfaction studies. The results showed that generally, the buying and selling process using the PPJB structure is legally deemed to have not occurred a juridical surrender (juridische levering) or physical submission (levering) in the sale and purchase. In order for a juridical and physical handover from the seller to the buyer, the buying and selling process with the PPJB must be followed up with a Sale and Purchase Deed (AJB. Related to Article 127 Letter B Permen ATR/Ka-BPN Number 16 of 2021 that interested parties can submit requests for recording agreements sale and purchase agreement or lease agreement on registered land with the Land Office; hence legally there is no legal effect of PPJB registration to the Land Office. Such registration does not strengthen or weaken the legal status of PPJB. Likewise, there are no legal sanctions when a PPJB is registered at the Land Office.